The oxygen potential on the scale surface of alloys at high temperature oxidation - Kawamura, Kenichi; Ani, Mohd Hanafi; Ueda, Mitsutoshi; Maruyama, Toshio (The Japan Society of Calorimetry and Thermal Analysis, 2010)
The driving force of the oxide scale growth on alloy is the difference in the oxygen potential between at the alloy/scale and the scale/atmosphere interfaces. When the mass transport in the oxide scale controls the growth of the oxide scale, we usually regards the oxygen potential at the scale/atmosphere interface as that of atmosphere. On the other hands, when the gas supply or the reaction controls the growth, the oxygen potential at the scale/atmosphere interface is different from that of atmosphere. This paper introduces the direct measurement for the oxygen potential on the scale surface.